Impaired human immunodeficiency virus type 1 replicative fitness in atypical viremic non-progressor individuals - Weber, Jan; Gibson, Richard M; Sácká, Lenka; Strunin, Dmytro; Hodek, Jan; Weberová, Jitka; Pávová, Marcela; Alouani, David J; Asaad, Robert; Rodriguez, Benigno; Lederman, Michael M; Quiñones-Mateu, Miguel E (AIDS research and therapy, 2017)
BACKGROUND: Progression rates from initial HIV-1 infection to advanced AIDS vary significantly among infected individuals. A distinct subgroup of HIV-1-infected individuals-termed viremic non-progressors (VNP) or controllers-do not seem to progress to AIDS, maintaining high CD4+T cell counts despite high levels of viremia for many years. Several studies have evaluated multiple host factors, including immune activation, trying to elucidate the atypical HIV-1 disease progression in these patients; however, limited work has been done to characterize viral factors in viremic controllers. METHODS: We analyzed HIV-1 isolates from three VNP individuals and compared the replicative fitness, near full-length HIV-1 genomes and intra-patient HIV-1 genetic diversity with viruses from three typical (TP) and one rapid (RP) progressor individuals. RESULTS: Viremic non-progressors and typical patients were infected for >10 years (range 10-17 years), with a mean CD4+T-cell count of 472 cells/mm3(442-529) and 400 cells/mm3(126-789), respectively. VNP individuals had a less marked decline in CD4+cells (mean -0.56, range -0.4 to -0.7 CD4+/month) than TP patients (mean -10.3, -8.2 to -13.1 CD4+/month). Interestingly, VNP individuals carried viruses with impaired replicative fitness, compared to HIV-1 isolates from the TP and RP patients (p < 0.05, 95% CI). Although analyses of the near full-length HIV-1 genomes showed no clear patterns of single-nucleotide polymorphisms (SNP) that could explain the decrease in replicative fitness, both the number of SNPs and HIV-1 population diversity correlated inversely with the replication capacity of the viruses (r = -0.956 andr = -0.878,p < 0.01, respectively). CONCLUSION: It is likely that complex multifactorial parameters govern HIV-1 disease progression in each individual, starting with the infecting virus (phenotype, load, and quasispecies diversity) and the intrinsic ability of the host to respond to the infection. Here we analyzed a subset of viremic controller patients and demonstrated that similar to the phenomenon observed in patients with a discordant response to antiretroviral therapy (i.e., high CD4+cell counts with detectable plasma HIV-1 RNA load), reduced viral replicative fitness seems to be linked to slow disease progression in these antiretroviral-naïve individuals.
Keywords: dlouhodobě přežívající nosiči HIV; HIV Infections; Humans; Virus Replication; genom virový; HIV infekce; sekvenční analýza DNA; genetická variace; lidé; HIV Long-Term Survivors; Sequence Analysis, DNA; Genetic Variation; Cohort Studies; lidé středního věku; genetická zdatnost; HIV-1; Male; replikace viru; Adult; dospělí; Genome, Viral; Genetic Fitness; Middle Aged; mužské pohlaví; kohortové studie